An All-Aqueous Thermally Regenerative Ammonia Battery Chemistry Using Cu(I, II) Redox Reactions. Issue 7 (13th July 2021) - Springer, Renaldo; Cross, Nicholas R.; Lvov, Serguei N.; Logan, Bruce E.; Gorski, Christopher A.; Hall, Derek M.
Abstract : Thermally regenerative ammonia batteries (TRABs) are electrochemical energy conversion devices that convert low-grade waste heat into electrical power. To date, reported TRABs have suffered from poor performance due to their reliance on dissolution and deposition redox reactions with transition metals. Here we present a new TRAB chemistry that uses ligands to stabilize aqueous Cu(I) and Cu(II) ions, thereby creating the first reported all-aqueous TRAB. Rotating disc electrode studies were conducted to evaluate thermodynamic and kinetic parameters of prospective anolyte and catholyte chemistries. The use of NH3 (aq) and Br − (aq) ligands resulted in a cell potential difference of 695 ± 2 mV with rate constants of 101 ± 5 μ m s −1 and 819 ± 236 μ m s −1, respectively. Single-cell tests achieved power densities up to 350 W m −2 which are the highest reported for single metal TRABs at 25 °C. Coulombic efficiencies exceeded 90% and their energy storage densities were two to four times of those reported for alternative TRAB chemistries.